Internet addiction and poor quality of life are significantly associated with suicidal ideation of senior high school students in Chongqing, China - Wo Wang; Dong Dong Zhou; Ming Ai; Xiao Rong Chen; Zhen Lv; Yan Huang; Li Kuang (PeerJ, 2019)
Background Adolescence is a vulnerable period of life, and many mental health and behavioral problems emerge during this particular period, including depression, internet addiction (IA), and suicidal behaviors. Poor quality of life (QOL) and IA have been found to be significantly associated with suicidal ideation (SI) among Chinese university students, of whom most have been adults. Nevertheless, their associations with SI are rarely studied among Chinese adolescents. The objective of this study was to examine these relationships in a representative adolescent sample of Chinese senior high school students, who are experiencing an enormous transition from childhood to adulthood. Methods By using multi-stage sampling, a total of 26,688 students were successfully recruited from 29 senior high schools of a very large City in western China, Chongqing municipality. In this cross-sectional online survey, students’ demographic and lifestyle characteristics were collected with a standardized questionnaire. The Young’s IA Test, the Chinese Six-item QOL questionnaire, and item 15 of the Symptom Checklist-90-R were used to measure IA, QOL, and SI, respectively. Results The 1-month prevalence of SI was 11.5% among students of senior high schools in Chongqing, China. Students with SI had significantly higher QOL scores (17.3 ± 3.7 vs. 13.7 ± 3.8, P < 0.001) and higher prevalence of IA (49.6% vs. 25.6%, P < 0.001) than those without SI. After controlling for demographic, lifestyle, and clinical covariates, IA (odd ratio (OR) = 1.15, P = 0.003) and a high QOL score (OR = 1.09, P < 0.001) remained significantly associated with SI. Conclusion Suicidal ideation is prevalent among Chinese adolescents and it is associated with IA and poor QOL. Measures aimed at reducing IA and improving QOL may help prevent suicidal behaviors among Chinese adolescents.